A method for preparing positive electrode material

Through the preparation method of conductive polymer coated with ferroal alkali metal salt, the problem of poor electronic conductivity of the positive electrode material of sodium ion battery is solved, the performance and stability are improved, the preparation process is simplified, and it is suitable for industrial production.

CN119176584BActive Publication Date: 2025-02-18SHENZHEN INST OF ADVANCED TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411686682.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-18
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The existing sodium ion battery positive electrode materials have poor electronic conductivity, resulting in poor performance, and initiators or catalysts are required during the preparation process, which increases production costs and side reactions, and is not suitable for industrial production.

Method used

By dispersing the alkali metal source, the iron source and the conductive polymer monomer in an acid solvent and stirring, a suspension is obtained, and the solvent is then removed, and then calcined after grinding to obtain a conductive polymer-coated ferroal alkali metal salt positive electrode material.

Benefits of technology

It achieves improved conductivity, enhances rate performance and cycle stability, simplifies the preparation process, reduces production costs, is suitable for large-scale industrial production, and improves the air stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119176584B_ABST
    Figure CN119176584B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of batteries, and specifically discloses a method for preparing a positive electrode material; the method for preparing the positive electrode material comprises the following steps: S1: mixing raw materials including an alkali metal source, an iron source, and a solvent, and then mixing them with a solution containing a conductive polymer monomer and an acid, and then removing the solvent to obtain a precursor; S2: grinding and calcining the precursor to obtain the positive electrode material; the positive electrode material is an alkali metal iron sulfate salt coated with a conductive polymer. The method for preparing the positive electrode material provided by the present invention has cheap and readily available synthetic raw materials, a simple and easy-to-operate preparation method, a short preparation cycle, high repeatability, and is suitable for large-scale industrial production. In addition, the preparation method of the present invention can achieve self-polymerization of the conductive polymer monomer without using any initiator or catalyst, and can avoid the influence of initiators and catalysts on the positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of batteries, and in particular relates to a method for preparing a positive electrode material. Background Art

[0002] The sodium-ion battery system has received widespread attention recently due to its abundant resources, low price, environmental friendliness, and similar electrochemical properties to lithium-ion batteries, providing a new option for electrochemical energy storage. At the same time, sodium-ion batteries have become a promising energy storage technology due to their relatively low cost and good cycle stability. The reported positive electrode materials for sodium-ion batteries mainly include layered oxides, Prussian blue systems, and polyanion systems. The electrochemical performance of sodium-ion batteries mainly depends on the structure and properties of electrode materials. It is generally believed that the performance of positive electrode materials (such as specific capacity, voltage, and cyclability) is the key factor affecting the energy density, safety, and cycle life of sodium-ion batteries. Therefore, the improvement and enhancement of the performance of positive electrode materials, as well as the development and exploration of new positive electrode materials have always been research hotspots in the field of sodium-ion batteries.

[0003] Sulfate system sodium ion battery cathode materials have a high working voltage, low raw material cost, and good development prospects. The iron-based polyanion cathode materials mainly involve Fe in the redox reaction process. 2+ / Fe 3+ The redox reaction between Fe 2+ / Fe 3+ The redox potential of the material directly affects the working voltage of the material. Due to the "inductive effect" of the polyanion group, the electronegative sulfate material has a voltage close to 3.8 V (vs. Na + / Na) redox potential, has become a research hotspot. However, the electronic conductivity of this type of compound is poor, and there is a problem that the intrinsic electronic conductivity is poor and affects the performance, and it is usually necessary to adopt composite / coating and other means for modification. The prior art needs to dissolve the raw materials in an organic solvent (such as dimethylformamide, isopropanol, ethanol and N-methylpyrrolidone) during coating, and at the same time, an initiator (such as ferric chloride or ammonium persulfate) or a catalyst is required to induce the polymer to polymerize on the surface of the positive electrode material. The post-processing steps increase, the production cost increases, there are many additives, and there are many side reactions. It is not suitable for industrial production, and the obtained positive electrode material has poor rate performance, poor cycle stability and low sodium storage capacity after being assembled into a battery, which seriously affects its industrialization process. Summary of the invention

[0004] In order to overcome at least one technical problem existing in the above-mentioned prior art, one of the objectives of the present invention is to provide a method for preparing a positive electrode material.

[0005] A second object of the present invention is to provide a battery.

[0006] The third object of the present invention is to provide a product.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] A first aspect of the present invention provides a method for preparing a positive electrode material, comprising the following steps:

[0009] S1: mixing raw materials including an alkali metal source, an iron source, and a solvent, and then mixing with a solution containing a conductive polymer monomer and an acid, and then removing the solvent to obtain a precursor;

[0010] S2: grinding and calcining the precursor to obtain the positive electrode material;

[0011] The positive electrode material is an alkali metal iron sulfate coated with a conductive polymer.

[0012] The preparation method of the present invention comprises the following steps: dispersing an alkali metal source, an iron source, a conductive polymer monomer, etc. in a certain amount of an acidic solvent and stirring the resulting mixture to obtain a suspension; removing the solvent in the suspension to obtain a precursor; and then grinding and calcining the precursor powder particles to obtain an alkali iron sulfate salt coated with a conductive polymer. The conductive polymer monomer self-polymerizes to form a conductive network and is coated on the surface of the alkali iron sulfate salt matrix, accelerating the transfer of electrons through abundant conductive channels, providing a fast charge transfer pathway, and facilitating the use of capacity and improving rate performance. On the other hand, the network structure is used to slow down the volume change during charge and discharge, thereby improving the cycle performance; and at the same time, the air is effectively isolated, thereby improving the air stability of the material.

[0013] Preferably, the alkali metal iron sulfate is selected from sodium iron sulfate, lithium iron sulfate or potassium iron sulfate.

[0014] Preferably, the conductive polymer monomer is at least one selected from pyrrole, aniline, 3,4-ethylenedioxythiophene, p-phenylenediamine, thiophene, acrylic acid, ethylene oxide, and polyvinyl alcohol.

[0015] Preferably, the acid is selected from at least one of formic acid, acetic acid and orthophosphoric acid.

[0016] Preferably, the mass concentration of the acid in the solution containing the conductive polymer monomer and the acid is 0-10 g / mL, but not 0, for example, its mass concentration can be selected from 0.1 g / mL, 0.5 g / mL, 1 g / mL, 2 g / mL, 3 g / mL, 4 g / mL, 5 g / mL, 6 g / mL, 7 g / mL, 8 g / mL, 9 g / mL, 10 g / mL. Further preferably, the mass concentration of the acid in the solution containing the conductive polymer monomer and the acid is 0-1 g / mL, but not 0.

[0017] Preferably, the ratio of the mass of the conductive polymer monomer to the total mass of the alkali metal source and the iron source is (0.001~50):100, for example, it can be selected from 0.001:100, 0.01:100, 0.1:100, 1:100, 5:100, 10:100, 15:100, 20:100, 25:100, 30:100, 35:100, 40:100, 45:100, 50:100; further preferably, the ratio of the mass of the conductive polymer monomer to the total mass of the alkali metal source and the iron source is (0.01~20):100.

[0018] Preferably, the molar ratio of the iron source to the alkali metal source is (0.5~5):1, for example, can be selected from 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1; further preferably, the molar ratio of the iron source to the alkali metal source is (1.5~3.5):1.

[0019] Preferably, the step of removing the solvent is performed by evaporating the solvent at 40-100°C, for example, the temperature can be selected from 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C; further preferably, the step of removing the solvent is performed by evaporating the solvent at 60-100°C.

[0020] Preferably, the step of removing the solvent is: first evaporating at 40-100° C. and then drying to remove the solvent.

[0021] Preferably, the time of the evaporation step is 0.1 to 20 h, for example, can be selected from 0.1 h, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h, 20 h; further preferably, the time of the evaporation step is 1 to 10 h.

[0022] Preferably, step S1 is: mixing raw materials including an alkali metal source, an iron source, and a solvent, and then mixing with a solution containing a conductive polymer monomer and an acid, heating and evaporating, and drying to remove the solvent to obtain a precursor. In the present invention, the step of removing the solvent includes two stages. In the first stage, during the heating and evaporation process, the solvent will evaporate from the reaction system to obtain a wet precursor; in the second stage, the drying step will further evaporate and remove the solvent in the wet precursor to obtain a dry precursor.

[0023] Preferably, the drying temperature is 40-200°C, for example, can be selected from 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C; further preferably, the drying temperature is 90-180°C.

[0024] Preferably, the drying time is 2 to 20 hours, for example, can be selected from 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h; further preferably, the drying time is 2 to 12h.

[0025] Preferably, the calcination temperature is 200-600°C, for example, can be selected from 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C; further preferably, the calcination temperature is 200-400°C.

[0026] Preferably, the calcination holding time is 2 to 48 hours, for example, can be selected from 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 22h, 24h, 25h, 26h, 28h, 30h, 32h, 34h, 36h, 38h, 40h, 42h, 44h, 46h, 48h; further preferably, the calcination holding time is 12 to 36h.

[0027] Preferably, the calcination heating rate is 0.5~10℃ / min, for example, can be selected from 0.5℃ / min, 1℃ / min, 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, 9℃ / min, 10℃ / min; further preferably, the calcination heating rate is 0.5~4℃ / min.

[0028] Preferably, the calcination atmosphere is selected from at least one of nitrogen, argon and hydrogen.

[0029] Preferably, the alkali metal source is selected from at least one of anhydrous sodium sulfate, sodium sulfate decahydrate, sodium bisulfate, sodium carbonate, sodium bicarbonate, sodium acetate, sodium nitrite, sodium oxalate, sodium persulfate, sodium hydroxide, sodium pyrosulfate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium pyrosulfite, sodium pyrophosphate, sodium hydrogen phthalate, sodium hydrogen oxalate, sodium sulfite, sodium sorbate, trisodium phosphate, sodium gluconate, and sodium oleate; further preferably, the alkali metal source is selected from at least one of anhydrous sodium sulfate, sodium sulfate decahydrate, and sodium bisulfate.

[0030] Preferably, the alkali metal source is selected from at least one of anhydrous lithium sulfate, lithium sulfate decahydrate, lithium hydrogen sulfate, lithium carbonate, lithium hydrogen carbonate, lithium acetate, lithium nitrite, lithium oxalate, lithium persulfate, lithium hydroxide, lithium pyrosulfate, lithium dihydrogen phosphate, dilithium hydrogen phosphate, lithium pyrosulfite, lithium pyrophosphate, lithium hydrogen phthalate, lithium hydrogen oxalate, lithium sulfite, lithium sorbate, trilithium phosphate, lithium gluconate, and lithium oleate; further preferably, the alkali metal source is selected from at least one of anhydrous lithium sulfate, lithium sulfate decahydrate, and lithium hydrogen sulfate.

[0031] Preferably, the alkali metal source is selected from at least one of anhydrous potassium sulfate, potassium sulfate decahydrate, potassium hydrogen sulfate, potassium carbonate, potassium bicarbonate, potassium acetate, potassium nitrite, potassium oxalate, potassium persulfate, potassium hydroxide, potassium pyrosulfate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, potassium pyrosulfite, potassium pyrophosphate, potassium hydrogen phthalate, potassium hydrogen oxalate, potassium sulfite, potassium sorbate, tripotassium phosphate, potassium gluconate, and potassium oleate; further preferably, the alkali metal source is selected from at least one of anhydrous potassium sulfate, potassium sulfate decahydrate, and potassium hydrogen sulfate.

[0032] Preferably, the iron source is selected from at least one of ferrous sulfate, ferrous oxide, ferrous chloride, ferrous sulfate monohydrate, ferrous sulfate tetrahydrate, ferrous sulfate heptahydrate, ferrous hydroxide, ferrous oxide, ferric chloride, and ferric hydroxide; further preferably, the iron source is selected from at least one of ferrous sulfate monohydrate, ferrous sulfate tetrahydrate, and ferrous sulfate heptahydrate.

[0033] Since the positive electrode material in the present invention contains an alkali metal iron sulfate salt, at least one of the iron source and the alkali metal source contains a group including a sulfate ion.

[0034] Preferably, the solvent is selected from at least one of water, methanol, ethanol, acetone, ethylene glycol, and pyridine; more preferably, the solvent is selected from at least one of methanol and ethanol.

[0035] A second aspect of the present invention provides a battery, comprising a positive electrode, wherein the positive electrode comprises a positive electrode material prepared by the preparation method described in the first aspect of the present invention.

[0036] Preferably, the positive electrode further comprises a current collector and a positive electrode material layer, and the positive electrode material layer is disposed on the surface of the current collector; the positive electrode material layer comprises the positive electrode material prepared by the preparation method described in the first aspect of the present invention, a conductive agent and a binder.

[0037] The third aspect of the present invention provides a product, comprising the battery described in the first aspect of the present invention, wherein the product is selected from a mobile electronic communication device, an electric vehicle, an electric bicycle, an energy storage battery, a power battery or an energy storage power station.

[0038] The beneficial effects of the present invention are as follows: the raw materials for synthesizing the positive electrode material provided by the present invention are cheap and readily available, the preparation method is simple and easy to operate, the preparation cycle is short, the repeatability is high, and the method is suitable for large-scale industrial production. In addition, the preparation method of the present invention can realize the self-polymerization of the conductive polymer monomer without using any initiator or catalyst, which can avoid the influence of the initiator and catalyst on the positive electrode material, and no by-products are generated during the preparation process and there is no pollution to the environment, which can simplify the post-processing process, reduce the production cost, and realize environmentally friendly production.

[0039] The positive electrode material prepared by the preparation method of the present invention has high conductivity and excellent chemical stability, and has excellent rate performance and cycle stability after being assembled into a battery. Specifically, after the positive electrode material is placed at room temperature for 30 days, the rate performance of the assembled battery and the capacity retention rate after 500 cycles are basically unchanged. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a field emission scanning electron microscope image of the sodium ion battery positive electrode material in Example 1. DETAILED DESCRIPTION

[0041] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially.

[0042] Example 1

[0043] This example provides a sodium ion battery positive electrode material, including a conductive polymer and a sodium ferric sulfate material; the conductive polymer is coated on the surface of the sodium ferric sulfate material, and the conductive polymer is polymerized from 3,4-ethylenedioxythiophene.

[0044] The preparation method of the positive electrode material of the sodium ion battery in this example comprises the following steps:

[0045] (1) Dissolve 56 µL of 3,4-ethylenedioxythiophene in 2 mL of ethanol, then add it to 4.7 mL of formic acid and stir to disperse evenly;

[0046] (2) Weigh 5.143 g of ferrous sulfate heptahydrate and 1.4204 g of anhydrous sodium sulfate in a molar ratio of 1.85:1, disperse them in 20 mL of water, and stir them magnetically until they are completely dissolved to obtain a mixed solution. Then add the solution in step (1), heat to 90°C, continue magnetic stirring, and then evaporate the solvent in a high-temperature water bath to remove the solvent to obtain a precursor;

[0047] (3) placing the precursor in step (2) into a forced air drying oven, setting the temperature to 130° C. and the drying time to 4 h for drying to obtain a composite sodium iron sulfate precursor;

[0048] (4) The dried precursor is ground and then subjected to low-temperature sintering. The low-temperature sintering step is to calcine at 350 °C for 24 h in an argon atmosphere with a heating rate of 2 °C / min to obtain the sodium ion battery positive electrode material in this example.

[0049] The morphology of the positive electrode material of the sodium ion battery in this example was tested using a field emission scanning electron microscope. The specific test picture is as follows: Figure 1 As shown. Figure 1 It can be seen that in the sodium ion battery positive electrode material in this example, the conductive polymer is uniformly coated on the surface of the sodium iron sulfate positive electrode material.

[0050] Example 2

[0051] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that sodium sulfate decahydrate is used in step (2) of this example to replace the anhydrous sodium sulfate in Example 1, and the molar ratio of ferrous sulfate heptahydrate to sodium sulfate decahydrate is 1.85:1.

[0052] Example 3

[0053] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that: in step (2) of this example, sodium bisulfate is used to replace the anhydrous sodium sulfate in Example 1, and the molar ratio of ferrous sulfate heptahydrate to sodium bisulfate is 1.85:1.

[0054] Example 4

[0055] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that: in step (2) of this example, ferrous sulfate monohydrate is used to replace ferrous sulfate heptahydrate in Example 1, and the molar ratio of ferrous sulfate monohydrate to anhydrous sodium sulfate is 1.85:1.

[0056] Example 5

[0057] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that: in step (2) of this example, ferrous sulfate tetrahydrate is used to replace ferrous sulfate heptahydrate in Example 1, and the molar ratio of ferrous sulfate tetrahydrate to anhydrous sodium sulfate is 1.85:1.

[0058] Example 6

[0059] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that: in step (2) of this example, ferrous sulfate monohydrate is used to replace the ferrous sulfate heptahydrate in Example 1, and sodium sulfate decahydrate is used to replace the anhydrous sodium sulfate in Example 1, and the molar ratio of ferrous sulfate monohydrate to sodium sulfate decahydrate is 1.85:1.

[0060] Example 7

[0061] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that: in step (2) of this example, ferrous sulfate monohydrate is used to replace the ferrous sulfate heptahydrate in Example 1, and sodium bisulfate is used to replace the anhydrous sodium sulfate in Example 1, and the molar ratio of ferrous sulfate monohydrate to sodium bisulfate is 1.85:1.

[0062] Example 8

[0063] The method for preparing the positive electrode material for a sodium ion battery in this example is different from that in Example 1 only in that the molar ratio of ferrous sulfate heptahydrate to anhydrous sodium sulfate in step (2) of this example is 1.5:1.

[0064] Example 9

[0065] The method for preparing the positive electrode material for a sodium ion battery in this example is different from that in Example 1 only in that the molar ratio of ferrous sulfate heptahydrate to anhydrous sodium sulfate in step (2) of this example is 1.75:1.

[0066] Example 10

[0067] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that the molar ratio of ferrous sulfate heptahydrate to anhydrous sodium sulfate in step (2) of this example is 1.95:1.

[0068] Embodiment 11

[0069] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that the molar ratio of ferrous sulfate heptahydrate to anhydrous sodium sulfate in step (2) of this example is 2:1.

[0070] Example 12

[0071] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that the molar ratio of ferrous sulfate heptahydrate to anhydrous sodium sulfate in step (2) of this example is 3.5:1.

[0072] Example 13

[0073] The method for preparing the positive electrode material for a sodium ion battery in this example is different from that in Example 1 only in that the molar ratio of ferrous sulfate heptahydrate to anhydrous sodium sulfate in step (2) of this example is 3.5:1.5.

[0074] Embodiment 14

[0075] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that an equal volume of pyrrole is used in step (1) of this example to replace the 3,4-ethylenedioxythiophene in Example 1.

[0076] Embodiment 15

[0077] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that an equimolar amount of p-phenylenediamine is used in step (1) of this example to replace the 3,4-ethylenedioxythiophene in Example 1.

[0078] Example 16

[0079] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that an equal molar amount of ethylene oxide is used in step (1) of this example to replace the 3,4-ethylenedioxythiophene in Example 1.

[0080] Embodiment 17

[0081] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that an equimolar amount of polyvinyl alcohol monomer is used in step (1) of this example to replace the 3,4-ethylenedioxythiophene in Example 1.

[0082] Embodiment 18

[0083] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that an equimolar amount of acrylic acid is used in step (1) of this example to replace the 3,4-ethylenedioxythiophene in Example 1.

[0084] Embodiment 19

[0085] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that deionized water is used in step (1) of this example to replace the ethanol in Example 1.

[0086] Embodiment 20

[0087] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that acetone is used in step (1) of this example to replace the ethanol in Example 1.

[0088] Embodiment 21

[0089] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that acetic acid is used in step (1) of this example to replace the formic acid in Example 1.

[0090] Embodiment 22

[0091] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that orthophosphoric acid is used in step (1) of this example to replace the formic acid in Example 1.

[0092] Embodiment 23

[0093] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that the amount of 3,4-ethylenedioxythiophene used in step (1) of this example is 100 μL.

[0094] Embodiment 24

[0095] The method for preparing the positive electrode material for a sodium ion battery in this example is different from that in Example 1 only in that the amount of 3,4-ethylenedioxythiophene used in step (1) of this example is 150 µL.

[0096] Embodiment 25

[0097] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that the heating temperature in step (2) of this example is 60°C.

[0098] Embodiment 26

[0099] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that the heating temperature in step (2) of this example is 80°C.

[0100] Embodiment 27

[0101] The method for preparing the positive electrode material for a sodium ion battery in this example is different from that in Example 1 only in that the heating temperature in step (2) of this example is 100°C.

[0102] Embodiment 28

[0103] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that the drying temperature in step (3) of this example is 90°C.

[0104] Embodiment 29

[0105] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that the drying temperature in step (3) of this example is 110°C.

[0106] Embodiment 30

[0107] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that the drying temperature in step (3) of this example is 150°C.

[0108] Embodiment 31

[0109] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that the drying temperature in step (3) of this example is 180°C.

[0110] Embodiment 32

[0111] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that the drying time in step (3) of this example is 2 h.

[0112] Embodiment 33

[0113] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that the drying time in step (3) of this example is 6 hours.

[0114] Embodiment 34

[0115] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that the drying time in step (3) of this example is 8 hours.

[0116] Embodiment 35

[0117] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that the drying time in step (3) of this example is 10 hours.

[0118] Embodiment 36

[0119] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that the drying time in step (3) of this example is 12 hours.

[0120] Embodiment 37

[0121] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that the calcination temperature in step (4) of this example is 200° C. and the calcination time is 48 h.

[0122] Embodiment 38

[0123] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that the calcination temperature in step (4) of this example is 250° C. and the calcination time is 40 h.

[0124] Embodiment 39

[0125] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that the calcination temperature in step (4) of this example is 300° C. and the calcination time is 36 h.

[0126] Embodiment 40

[0127] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that the calcination temperature in step (4) of this example is 400°C.

[0128] Embodiment 41

[0129] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that the calcination time in step (4) of this example is 12 h.

[0130] Embodiment 42

[0131] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that the calcination time in step (4) of this example is 18 hours.

[0132] Embodiment 43

[0133] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that the calcination time in step (4) of this example is 30 h.

[0134] Embodiment 44

[0135] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that the calcination time in step (4) of this example is 36 hours.

[0136] Embodiment 45

[0137] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that the heating rate in step (4) of this example is 0.5°C / min.

[0138] Embodiment 46

[0139] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that the heating rate in step (4) of this example is 1°C / min.

[0140] Embodiment 47

[0141] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that the heating rate in step (4) of this example is 1.5° C. / min.

[0142] Embodiment 48

[0143] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that the heating rate in step (4) of this example is 2.5°C / min.

[0144] Embodiment 49

[0145] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that the calcination atmosphere in step (4) of this example is nitrogen.

[0146] Embodiment 50

[0147] The preparation method of the sodium ion battery positive electrode material in this example is different from that in Example 1 only in that the calcination atmosphere in step (4) of this example is a mixture of argon and hydrogen in a volume ratio of 9.5:0.5.

[0148] Embodiment 51

[0149] This example provides a sodium ion half-cell, and the positive electrode active material used in the sodium ion half-cell is the sodium ion battery positive electrode material prepared in Example 1.

[0150] The sodium ion half-cell in this example is prepared by a preparation method comprising the following steps:

[0151] (1) Preparation of battery positive electrode: Add positive electrode active material powder, carbon black, and polyvinylidene fluoride to an appropriate amount of N-methylpyrrolidone in a mass ratio of 7:2:1, and grind thoroughly to obtain a uniform flowing slurry; apply the slurry evenly on the surface of carbon-coated aluminum foil and then vacuum dry. Cut the dried electrode sheet into discs with a diameter of 10 mm, compact them and use them as battery positive electrode sheets for later use;

[0152] (2) Preparation of battery negative electrode: Press the sodium metal into thin sheets and cut them into discs with a diameter of 12 mm to serve as the battery negative electrode;

[0153] (3) Battery assembly: A glass fiber film was used as a separator and 1 mol / L sodium hexafluorophosphate dissolved in a mixed solvent of propylene carbonate and fluoroethylene carbonate (volume ratio 95:5) was used as an electrolyte. In an inert gas-protected glove box, the prepared positive electrode, separator and negative electrode were stacked tightly in sequence. The electrolyte was added dropwise to completely soak the separator. The stacked parts were then encapsulated in a button-type battery casing to complete the battery assembly and obtain the sodium ion half-cell in this example.

[0154] Embodiment 52-100

[0155] The sodium ion half-cells in Examples 52-100 differ from those in Example 51 only in that the sodium ion half-cells in Examples 52 to 100 respectively use the sodium ion battery positive electrode materials prepared in Examples 2-50 as positive electrode active materials.

[0156] Comparative Example 1

[0157] This example provides a sodium ion battery positive electrode material, and the preparation method thereof comprises the following steps:

[0158] (1) Weigh 5.143 g of ferrous sulfate and 1.4204 g of anhydrous sodium sulfate in a molar ratio of 1.85:1, disperse them in 20 mL of water, stir them magnetically until they are completely dissolved, and obtain a mixed solution. Heat the solution to 90 °C with continuous magnetic stirring, and evaporate the solvent in a high-temperature water bath to obtain a precursor.

[0159] (2) placing the precursor in step (1) into a forced air drying oven, setting the drying temperature to 130° C. and the drying time to 4 h to obtain a composite sodium iron sulfate precursor;

[0160] (3) The dried precursor is ground and then sintered at low temperature. It is calcined at 350°C for 24 h in an argon atmosphere at a heating rate of 2°C / min to obtain the sodium ion battery positive electrode material in this example.

[0161] Comparative Example 2

[0162] This example provides a sodium ion battery positive electrode material, and the preparation method thereof is different from that of Example 1 only in that formic acid is not added in step (1) of this example.

[0163] Comparative Example 3

[0164] This example provides a sodium ion half-cell, and the preparation method thereof differs from that of Example 51 only in that this example uses the sodium ion battery positive electrode material in Comparative Example 1 as the positive electrode active material.

[0165] Comparative Example 4

[0166] This example provides a sodium ion half-cell, and the preparation method thereof differs from that of Example 51 only in that this example uses the sodium ion battery positive electrode material in Comparative Example 2 as the positive electrode active material.

[0167] Performance Testing

[0168] The constant current charge and discharge performance of the sodium ion half-cells prepared in Examples 51 to 100 and Comparative Examples 3 to 4 was tested respectively, and the specific test method was as follows: The constant current charge and discharge test used the BTSDA test system of Shenzhen Xinwei Electronics Co., Ltd., the environment was a constant temperature and humidity room (temperature was 25 ° C, humidity was 35%), the test voltage range was 2-4.5 V, 1 C = 120 mAh / g, and the initial discharge specific capacity at 0.1C was in the range of 105-110 mAh / g. The specific capacity of the sodium ion half-cell measured by the above test method after 10 cycles at 5C and the capacity retention rate after 500 cycles at 1 C current density are shown in Table 1. After the sodium ion battery positive electrode materials prepared in Examples 1 to 50 and Comparative Examples 1 to 2 were exposed to air for 30 days, they were assembled into sodium ion half-cells according to the method in Example 51, and then their specific capacity after 10 cycles at 5C and their capacity retention rate after 500 cycles at 1 C current density were tested. The specific test results are shown in Table 1.

[0169] Table 1 Constant current charge and discharge performance test results of sodium ion half-cell

[0170]

[0171] As can be seen from Table 1, the specific capacity of the sodium ion half-cells assembled from the sodium ion battery positive electrode materials provided in Examples 1 to 50 of the present invention at 5C cycles for 10 cycles and the capacity retention rate at 1C cycles for 500 cycles are significantly better than those in Comparative Examples 3 to 4. In addition, after the sodium ion battery positive electrode materials in Examples 51 to 100 were exposed to air for 30 days, the specific capacity and 500-cycle capacity retention rate of the assembled sodium ion half-cells did not change significantly, while the specific capacity and 500-cycle capacity retention rate of the battery assembled from the positive electrode materials in Comparative Examples 3 to 4 were significantly reduced after being exposed to air for 30 days, indicating that the sodium ion battery positive electrode material provided by the present invention has better air stability.

[0172] In summary, the present invention provides a sodium ion battery positive electrode material, in which the conductive polymer monomer self-polymerizes to form a conductive network and is uniformly coated on the surface of the sodium ferric sulfate matrix. On the one hand, the electronic conductivity of the material is improved, which is helpful for the capacity to be exerted and the rate performance to be improved; on the other hand, the volume change during the cycle is suppressed by the network structure, and the cycle performance is improved; at the same time, the air is effectively isolated, and the air stability of the material is improved. In addition, the preparation method of the sodium ion battery positive electrode material provided by the present invention is simple, and the conductive polymer monomer is uniformly self-polymerized on the surface of the sodium ferric sulfate matrix without adding an initiator. The preparation method has high repeatability, and the generation of by-products is reduced during the reaction without increasing the process and equipment costs. It is highly environmentally friendly, helps to reduce resource shortages and environmental pollution, and has a bright prospect for industrial production.

[0173] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A method for preparing a positive electrode material, characterized in that: The following steps are involved: S1: mixing raw materials including an alkali metal source, an iron source, and a solvent, and then mixing with a solution containing a conductive polymer monomer and an acid, and removing the solvent to obtain a precursor; S2: grinding and calcining the precursor to obtain the positive electrode material; The positive electrode material is an alkali metal iron sulfate coated with a conductive polymer; The acid is selected from at least one of formic acid, acetic acid, and orthophosphoric acid; The step of removing the solvent comprises evaporating the solvent at 40-100° C. The conductive polymer monomer is selected from at least one of pyrrole, aniline, 3,4-ethylenedioxythiophene, p-phenylenediamine, thiophene, acrylic acid, and ethylene oxide; The mass concentration of the acid in the solution containing the conductive polymer monomer and the acid is 0-10 g / mL, but not 0.

2. The method for preparing the positive electrode material according to claim 1, characterized in that: The ratio of the mass of the conductive polymer monomer to the total mass of the alkali metal source and the iron source is (0.001-50): 100; And / or, the molar ratio of the iron source to the alkali metal source is (0.5~5):

1.

3. The method for preparing the positive electrode material according to claim 1, characterized in that: The calcining step has at least one of the following characteristics: (a) the calcination temperature is 200-600°C; (b) the calcination holding time is 2 to 48 hours; (c) the calcination heating rate is 0.5-10°C / min; (d) The calcination atmosphere is at least one selected from nitrogen, argon and hydrogen.

4. The method for preparing the positive electrode material according to claim 1 or 2, characterized in that: The alkali metal source is selected from at least one of anhydrous sodium sulfate, sodium sulfate decahydrate, sodium bisulfate, sodium carbonate, sodium bicarbonate, sodium acetate, sodium nitrite, sodium oxalate, sodium persulfate, sodium hydroxide, sodium pyrosulfate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium pyrosulfite, sodium pyrophosphate, sodium hydrogen phthalate, sodium hydrogen oxalate, sodium sulfite, sodium sorbate, trisodium phosphate, sodium gluconate, and sodium oleate; Or, the alkali metal source is selected from at least one of anhydrous lithium sulfate, lithium sulfate decahydrate, lithium hydrogen sulfate, lithium carbonate, lithium hydrogen carbonate, lithium acetate, lithium nitrite, lithium oxalate, lithium persulfate, lithium hydroxide, lithium pyrosulfate, lithium dihydrogen phosphate, dilithium hydrogen phosphate, lithium pyrosulfite, lithium pyrophosphate, lithium hydrogen phthalate, lithium hydrogen oxalate, lithium sulfite, lithium sorbate, trilithium phosphate, lithium gluconate, and lithium oleate; Or, the alkali metal source is selected from at least one of anhydrous potassium sulfate, potassium sulfate decahydrate, potassium hydrogen sulfate, potassium carbonate, potassium bicarbonate, potassium acetate, potassium nitrite, potassium oxalate, potassium persulfate, potassium hydroxide, potassium pyrosulfate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, potassium pyrosulfite, potassium pyrophosphate, potassium hydrogen phthalate, potassium hydrogen oxalate, potassium sulfite, potassium sorbate, tripotassium phosphate, potassium gluconate, and potassium oleate.

5. The method for preparing the positive electrode material according to claim 1, characterized in that: The iron source is selected from at least one of ferric sulfate, ferrous oxide, ferrous chloride, ferrous sulfate monohydrate, ferrous sulfate tetrahydrate, ferrous sulfate heptahydrate, ferrous hydroxide, ferrous oxide, ferric chloride, and ferric hydroxide; And / or, the solvent is selected from at least one of water, methanol, ethanol, acetone, ethylene glycol and pyridine.

6. Use of the method for preparing the positive electrode material according to any one of claims 1 to 5 in preparing a battery or a product containing a battery, characterized in that: The product is selected from mobile electronic communication equipment, electric vehicles, electric bicycles, energy storage batteries, power batteries or energy storage power stations.

Citation Information

Patent Citations

  • Sodium ion positive electrode material and preparation method and application thereof

    CN114400309A

  • Sodium ion composite positive electrode material and preparation method and application thereof

    CN115642237A

  • Sodium ferric sulfate positive electrode material as well as preparation method and application thereof

    CN116613288A

  • Sulfate sodium ion battery positive electrode material and preparation method thereof

    CN117174846A

  • Positive pole piece of sodium ion battery, preparation method of positive pole piece and sodium ion battery

    CN117276472A